Estimating Global Ecosystem Isohydry/Anisohydry Using Active and Passive Microwave Satellite Data. Issue 12 (26th December 2017) - Li, Yan; Guan, Kaiyu; Gentine, Pierre; Konings, Alexandra G.; Meinzer, Frederick C.; Kimball, John S.; Xu, Xiangtao; Anderegg, William R. L.; McDowell, Nate G.; Martinez‐Vilalta, Jordi; Long, David G.; Good, Stephen P.
Abstract: The concept of isohydry/anisohydry describes the degree to which plants regulate their water status, operating from isohydric with strict regulation to anisohydric with less regulation. Though some species level measures of isohydry/anisohydry exist at a few locations, ecosystem‐scale information is still largely unavailable. In this study, we use diurnal observations from active (Ku‐Band backscatter from QuikSCAT) and passive (X‐band vegetation optical depth (VOD) from Advanced Microwave Scanning Radiometer on EOS Aqua) microwave satellite data to estimate global ecosystem isohydry/anisohydry. Here diurnal observations from both satellites approximate predawn and midday plant canopy water contents, which are used to estimate isohydry/anisohydry. The two independent estimates from radar backscatter and VOD show reasonable agreement at low and middle latitudes but diverge at high latitudes. Grasslands, croplands, wetlands, and open shrublands are more anisohydric, whereas evergreen broadleaf and deciduous broadleaf forests are more isohydric. The direct validation with upscaled in situ species isohydry/anisohydry estimates indicates that the VOD‐based estimates have much better agreement than the backscatter‐based estimates. The indirect validation with prior knowledge suggests that both estimates are generally consistent in that vegetation water status of anisohydric ecosystems more closely tracks environmental fluctuations of water availability and demand than their isohydric counterparts. However, uncertainties still exist in the isohydry/anisohydry estimate, primarily arising from the remote sensing data and, to a lesser extent, from the methodology. The comprehensive assessment in this study can help us better understand the robustness, limitation, and uncertainties of the satellite‐derived isohydry/anisohydry estimates. The ecosystem isohydry/anisohydry has the potential to reveal new insights into spatiotemporal ecosystem response to droughts. Key Points: Isohydry/anisohydry estimates from backscatter and VOD data show reasonable agreement at low and middle latitudes but diverge at high latitudes Grasslands, croplands, and open shrublands are more anisohydric, while evergreen broadleaf and deciduous broadleaf forests are more isohydric VOD‐based isohydry/anisohydry estimates show better agreement with upscaled in situ measurements than backscatter‐based estimates